GDP Nowcasting: assessing business cycle conditions in Argentina - D'Amato, Laura Inés (2014)
Having a correct assessment of current business cycle conditions is one of the mayor challenges for monetary policy conduct. Given that GDP figures are available with a significant delay, central banks are increasingly using Nowcasting as a useful tool for having an immediate perception of economic conditions. Thus we develop a GDP growth nowcasting exercise using two approaches: bridge equations and a dynamic factor model. Both outperform a typical AR(1) benchmark in terms of forecasting accuracy. Moreover, the factor model outperforms the nowcast using bridge equations. Following Giacomini and White (2004) we confirm that these differences are statistically significant.